Nailfold digital capillaroscopic findings in patients with diffuse and limited cutaneous systemic sclerosis - Shenavandeh, Saeedeh (Reumatologia, 2017)
BACKGROUND: Systemic sclerosis (SSc) is a chronic disease with microvascular damage. Nailfold capillaroscopy is a non-invasive method used for evaluating capillaries in SSc. Its findings could be related to the internal organ involvement and SSc course. In this study, we aimed to determine the association of the capillaroscopic patterns of nailfold capillaries with the disease subtypes of SSc, disease duration, and clinical manifestations. MATERIAL AND METHODS: Seventy patients with SSc (15 cases with diffuse cutaneous SSc [DcSSc] and 55 patients with limited SSc [LcSSc]) were studied. The patients were classified into early and intermediate/late DcSSc and LcSSc regarding their disease duration. The capillaroscopy findings were classified into normal, ‘early’, ‘active’ and ‘late’ scleroderma patterns, and ‘non-specific’ changes. The association of the nailfold capillaroscopy changes and their components with clinical manifestations was also studied. RESULTS: We studied 15 DcSSc and 55 LcSSc patients. No association was found between the patterns of capillaroscopic changes and these subtypes. There were 8 early DcSSc, 7 intermediate/late DcSSc, 34 early LcSSc, and 21 intermediate/late LcSSc patients. In patients with LcSSc, the ‘early’ scleroderma pattern of capillaroscopy was associated with early disease based on duration. We found a direct association between some capillary components and some clinical findings. Also, some capillaroscopic components had an inverse association with some clinical manifestations. CONCLUSIONS: We found no association between the patterns of capillaroscopy and SSc subtypes; early scleroderma pattern of capillaroscopy was significantly associated with early LcSSc, compatible with the slower course of the disease in LcSSc. Subtle changes, capillary elongation, and capillary tortuosity had an inverse association with clinical manifestations and might be considered as good prognostic factors.